1989
DOI: 10.1021/bi00444a009
|View full text |Cite
|
Sign up to set email alerts
|

Extrinsic 33-kilodalton protein of spinach oxygen-evolving complexes: kinetic studies of folding and disulfide reduction

Abstract: The 33-kDa protein is one of the three extrinsic proteins in the oxygen-evolving photosystem II complexes. The protein has one intrachain disulfide bond. On reduction of this disulfide bond, the protein was unfolded and lost its activity. On the basis of the unfolding equilibrium curve obtained by using guanidine hydrochloride, the free energy change of unfolding in the absence of guanidine hydrochloride was estimated to be 4.4 kcal/mol using the Tanford method [Tanford, C. (1970) Adv. Protein Chem. 24, 1-95] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
56
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(64 citation statements)
references
References 30 publications
8
56
0
Order By: Relevance
“…Since the 23-kDa protein cannot directly associate with the 33-kDa protein in solution (24), these results suggest that binding of the 33-kDa protein to PSII alters the conformation of the protein itself which is essential for binding of the 23-kDa protein. The occurrence of a structural change of the protein is consistent with results of pH-dependent structural changes (38), effects of genetic or chemical modification of its disulfide-forming cysteines (39,40), or the effects of conformational constrains resulting from other amino acid substitutions (41).…”
Section: Characterization Of Intramolecularly Cross-linked 33-kda Prosupporting
confidence: 69%
See 1 more Smart Citation
“…Since the 23-kDa protein cannot directly associate with the 33-kDa protein in solution (24), these results suggest that binding of the 33-kDa protein to PSII alters the conformation of the protein itself which is essential for binding of the 23-kDa protein. The occurrence of a structural change of the protein is consistent with results of pH-dependent structural changes (38), effects of genetic or chemical modification of its disulfide-forming cysteines (39,40), or the effects of conformational constrains resulting from other amino acid substitutions (41).…”
Section: Characterization Of Intramolecularly Cross-linked 33-kda Prosupporting
confidence: 69%
“…Two Cys residues (Cys 28 and Cys 51 ) of the protein form a disulfide bond important for maintaining the functional structure of the protein (40,45,47). The secondary structural analysis of the 33-kDa protein in solution by far-UV CD spectroscopy revealed that the protein contains a large proportion of ā¤-sheet and a relatively small amount of ā£-helical structure (48 (27).…”
Section: Characterization Of Intramolecularly Cross-linked 33-kda Promentioning
confidence: 99%
“…Interestingly, PsbO, a lumenal subunit of PSII required for stable assembly of the OEC, was shown to carry a single intramolecular disulfide that is strictly conserved in cyanobacteria and photosynthetic eukaryotes. In vitro studies established that this disulfide bond is critical to maintain the tertiary structure of PsbO (Tanaka et al, 1989;Betts , 1996;Wyman and Yocum, 2005). In chloroplast lumenal extracts, reduction of the disulfide in PsbO1 and PsbO2 targets the proteins for degradation.…”
Section: The Redox Activity Of Lto1 Is Required For the Assembly Of Psiimentioning
confidence: 99%
“…On the basis of its specific thermostability, acidic isoelectric point, and anomalous electrophoretic mobility, MSP was classified as a "natively unfolded" (7) protein or a "molten globule" (8). Soluble MSP unfolds extremely easily in the presence of 2 M Gdn-HCl or under relatively low pressure (about 160-180 MPa) (9,10). The crystal structure of PSII and studies of pH-induced structural changes in MSP suggested that MSP might provide a pathway for transporting protons from the catalyzing site of oxygen evolution to the lumen (11)(12)(13).…”
mentioning
confidence: 99%